Diet and Current Asthma Symptoms in School-Aged Children from Oropeza Province -Chuquisaca, Bolivia - María Teresa Solis-Soto; Armando Patiño; Dennis Nowak; Katja Radon (Open Journal of Asthma - Peertechz Publications, 2017)
Background: Several studies have linked dietary intake and asthma symptoms, nevertheless the results are still inconclusive and data from developing country are scarce. Objective: To assess the association of Food patterns and current asthma symptoms in school-aged children from rural and urban areas of Oropeza Province - Bolivia. Methods: A total of 1655 children attending the fifth elementary grade were invited to participate in a cross-sectional study in rural and urban areas of Oropeza province. Current Asthma symptoms were defi ned following the International Study of Asthma and Allergies in Childhood (ISSAC) recommendation (written and video questionnaire). Food patterns were defined using the ISAAC environmental  questionnaire. The Mediterranean diet (MD) score was calculated based on this information. Crude and adjusted logistic regression models were calculated including age, sex and place of living. Results: The age range was between 9 - 15 years (Median 11), and 47.9% were male. Current asthma symptoms were reported in a 17% considering the written questionnaire (WQ) and in a 6% considering the video questionnaire (VQ). Higher consumption of nuts [(p=0.01, aOR= 1.6(1.1-2.2)], corn [(p=0.03, aOR=1.5(1.0-2.2)] and fast food [(p=0.06, aOR= 1.4(1.0-2.0)] showed positive association with current asthma symptoms. Greater adherence to the MD was associated with lower risk of asthma symptoms. Conclusion: Promotion of healthy food patterns in children is needed in order to avoid the rapid increase of non-communicable diseases in this region.